2023
DOI: 10.1186/s12884-023-05486-9
|View full text |Cite
|
Sign up to set email alerts
|

Application of machine learning to identify risk factors of birth asphyxia

Abstract: Background Developing a prediction model that incorporates several risk factors and accurately calculates the overall risk of birth asphyxia is necessary. The present study used a machine learning model to predict birth asphyxia. Methods Women who gave birth at a tertiary Hospital in Bandar Abbas, Iran, were retrospectively evaluated from January 2020 to January 2022. Data were extracted from the Iranian Maternal and Neonatal Network, a valid natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…It was tested and validated by Google AI using a large training dataset of 128,175 and two separate publicly available datasets (Gulshan et al, 2016 , 2019 ). ML models are also being trained to identify newborns with risk of birth asphyxia (Onu et al, 2017 ; Sachin et al, 2017 ; Darsareh et al, 2023 ). Given the high neonatal mortality in low and middle income countries, this could prove to be a revolutionary application of AI in such circumstances.…”
Section: Applications Of Ai In Clinical Medicinementioning
confidence: 99%
“…It was tested and validated by Google AI using a large training dataset of 128,175 and two separate publicly available datasets (Gulshan et al, 2016 , 2019 ). ML models are also being trained to identify newborns with risk of birth asphyxia (Onu et al, 2017 ; Sachin et al, 2017 ; Darsareh et al, 2023 ). Given the high neonatal mortality in low and middle income countries, this could prove to be a revolutionary application of AI in such circumstances.…”
Section: Applications Of Ai In Clinical Medicinementioning
confidence: 99%
“…[12,13] Various international studies found that multiple risk factors: socio-demographic (mother's age, residence, mother's marital status, educational status, occupation), antepartum (antenatal care [ANC] follow up, parity, history of prior neonatal death, pre-eclampsia), intrapartum (prolonged labor, status of amniotic fluid, cephalopelvic disproportion), neonatal (preterm babies, birth weight, gestational age) are associated with NA. [14][15][16][17][18] However, information related to determinants of neonata asphyxia in Hainan referral hospitals of China, is limited. Therefore, the aim of this study was to identify women at risk of NA by combining multiple factors, minimize the rate of NA, and lighten the burden of family and society by improving maternal and neonatal management.…”
Section: Introductionmentioning
confidence: 99%